2014
DOI: 10.1098/rspb.2013.2615
|View full text |Cite
|
Sign up to set email alerts
|

Competition induces allelopathy but suppresses growth and anti-herbivore defence in a chemically rich seaweed

Abstract: Many seaweeds and terrestrial plants induce chemical defences in response to herbivory, but whether they induce chemical defences against competitors (allelopathy) remains poorly understood. We evaluated whether two tropical seaweeds induce allelopathy in response to competition with a reef-building coral. We also assessed the effects of competition on seaweed growth and seaweed chemical defence against herbivores. Following 8 days of competition with the coral Porites cylindrica, the chemically rich seaweed G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 51 publications
1
35
1
Order By: Relevance
“…This finding is consistent with the idea that allelochemicals-just as herbivore defense (Herms and Mattson 1992;Karban 2011)-are metabolically costly, and that there exists a tradeoff between resource allocation to growth versus allelopathy (see also Rasher and Hay 2014). Our results are in line with Kovarova et al (2010Kovarova et al ( , 2011 who also found that the production of secondary compounds in knotweed depends on nutrient supply.…”
Section: Discussionsupporting
confidence: 95%
“…This finding is consistent with the idea that allelochemicals-just as herbivore defense (Herms and Mattson 1992;Karban 2011)-are metabolically costly, and that there exists a tradeoff between resource allocation to growth versus allelopathy (see also Rasher and Hay 2014). Our results are in line with Kovarova et al (2010Kovarova et al ( , 2011 who also found that the production of secondary compounds in knotweed depends on nutrient supply.…”
Section: Discussionsupporting
confidence: 95%
“…The roots of Centaurea diffusa increase release of 8-hydroxyquinoline under iron limitation [10]. Eight days of competition induce the seaweed Galaxaura filamentosa to increase the release of allelochemicals [43]. Thus, future studies with more realistic allelochemical inputs and more ecologically relevant interactions between plants are required to enhance our understanding of the complex allelopathy between invasive and native plants.…”
Section: Discussionmentioning
confidence: 97%
“…shading, abrasion, sediment trapping) and/or chemically or microbially mediated [23,24,26,[46][47][48][49]. Prior studiesconducted on these same reefs detected no evidence that Sargassum, its lipid-soluble extracts or inert Sargassum mimics caused bleaching or visible damage to common corals [24,25,38,44], but previous assays did not evaluate effects on coral growth. Our findings are consistent with earlier studies that report reductions in coral growth because of competition with Sargassum sp.…”
Section: Discussionmentioning
confidence: 99%
“…shading, abrasion, overgrowth) and/ or chemical (i.e. allelopathy) mechanisms to directly reduce coral recruitment, growth, survival and fecundity [22][23][24][25]. Coral-algal interactions may also suppress corals indirectly by promoting virulent bacteria [26,27], or by stressing corals in ways that attract corallivores that further damage competing corals [28].…”
Section: Introductionmentioning
confidence: 99%